UHPC-filled duct connections for accelerated bridge construction of RC columns in high seismic zones. (15th September 2015) - Tazarv, Mostafa; Saiidi, M. Saiid
Highlights: A new moment connection was developed for precast bridge columns in high seismic zones. UHPC was incorporated as duct filler to reduce bar embedment length. No UHPC-filled duct connection damage was observed even after 12% drift ratio cycles. UHPC-filled duct connections are suitable for both ends of bridge columns. A simple method was developed to include bond–slip effect in analyses. Abstract: Substantial attention is being paid to accelerated bridge construction (ABC) in the United States because ABC offers many advantages such as shorter onsite construction time, lower traffic impact, and higher quality structural members. Prefabricated bridge elements and systems are one of the most important ABC components. However, scarcity of seismic performance data for prefabricated element connections has limited the application of ABC in high seismic zones. In this paper, seismic performance of a new column-to-footing connection was experimentally investigated by cyclic testing of a half-scale precast reinforced concrete bridge column connected to the footing incorporating an ultra-high performance concrete (UHPC) filled duct connection. The seismic performance of the test model was comprehensively compared with a reference cast-in-place model. Furthermore, connection performance of another half-scale precast bridge column utilizing this type of connection was presented. The former model was design and tested to specifically evaluate the seismic performance of the column utilizing new column-to-footing connection and the latter column was built with eight different materials to investigate the seismic performance of a low-damage precast column detailing for high seismic regions. Nevertheless, UHPC-filled duct connections were incorporated in the column-to-footing connections of the both test models. The test results showed that the UHPC-filled duct connections were emulative of the conventional connection. An analytical model was developed using a finite element computer program to simulate cyclic response of the column. The model incorporated a new analytical technique to include the effect of bond–slip through a modified stress–strain relationship for reinforcing steel. The calculated and measured force–displacement relationships of the column showed good correlation.